Priorities, barriers, and facilitators for nutrition-related care for autistic children: a qualitative study comparing interdisciplinary health professional and parent perspectives - Blaine, Rachel E.; Blaine, Kevin P.; Cheng, Katie; Banuelos, Cynthia; Leal, Aaron (Frontiers in Pediatrics, 2023)
Introduction Children with autism spectrum disorder often face nutrition-related challenges, such as food selectivity, gastrointestinal issues, overweight and obesity, and inadequate nutrient intake. However, the role of routine nutrition-related screening or care by interdisciplinary health professionals is not well understood. This study aimed to compare the beliefs of health professionals with those of parents of autistic children regarding high-priority nutrition-related challenges, barriers and facilitators to care, and desired education and resources related to nutrition for autistic children. Participants Interdisciplinary health professionals (n = 25) (i.e., pediatricians, occupational therapists, speech-language pathologists, board certified behavior analysts, registered dietitians) and parents of autistic children (n = 22). Methods The study used semi-structured phone interviews, which were recorded, transcribed, verified, and double-coded using the Framework Method. Results Thematic analysis of transcripts revealed that while health professionals and parents of autistic children shared some perspectives on nutrition-related challenges and care, they also had distinct viewpoints. Parents emphasized the importance of addressing food selectivity, behavioral eating challenges, sensory issues, and sleep disturbances affecting appetite. Both groups acknowledged the need for tailored support, access to an interdisciplinary care team, and reasonable expectations. Some health professionals perceived parents as lacking motivation or the ability to make changes. In contrast, many parents felt that health professionals lacked the knowledge and motivation to take nutrition or growth concerns seriously. Health professionals acknowledged that their lack of knowledge or capacity to provide nutrition education or referrals was a common barrier to care, particularly given limited community resources. Discussion Health professionals who serve autistic children are motivated to address nutrition-related challenges but lack resources related to nutrition. To promote better health outcomes for autistic children, professionals should identify and support parent motivations around nutrition-related care. Both groups expressed interest in accessing autism-specific resources for education, referral, and screening guidance. Future research could explore the development of healthcare training models that improve the competency of health professionals in providing nutrition care and referral for autistic children.